2021
DOI: 10.1038/s41598-021-00942-y
|View full text |Cite
|
Sign up to set email alerts
|

CYP3A-status is associated with blood concentration and dose-requirement of tacrolimus in heart transplant recipients

Abstract: High inter-individual variability in tacrolimus clearance is attributed to genetic polymorphisms of CYP3A enzymes. However, due to CYP3A phenoconversion induced by non-genetic factors, continuous changes in tacrolimus-metabolizing capacity entail frequent dose-refinement for optimal immunosuppression. In heart transplant recipients, the contribution of patients’ CYP3A-status (CYP3A5 genotype and CYP3A4 expression) to tacrolimus blood concentration and dose-requirement was evaluated in the early and late post-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Indeed, the CYP3A5*1 allele associated with extensive CYP3A5 metabolism has been shown to occur more frequently in individuals of black race, whereas the inactive CYP3A5*3 is the predominant allele in the white population 22,23 . Genetic differences in CYP3A5 have previously been shown to greatly alter the required therapeutic tacrolimus dose in both children and adults 24–27 . Interestingly, in the absence of CYP3A5 genotype data due to the retrospective nature of the current study, the impact of race was observed to decrease, rather than increase, the elimination of tacrolimus in the current study population.…”
Section: Discussionmentioning
confidence: 59%
“…Indeed, the CYP3A5*1 allele associated with extensive CYP3A5 metabolism has been shown to occur more frequently in individuals of black race, whereas the inactive CYP3A5*3 is the predominant allele in the white population 22,23 . Genetic differences in CYP3A5 have previously been shown to greatly alter the required therapeutic tacrolimus dose in both children and adults 24–27 . Interestingly, in the absence of CYP3A5 genotype data due to the retrospective nature of the current study, the impact of race was observed to decrease, rather than increase, the elimination of tacrolimus in the current study population.…”
Section: Discussionmentioning
confidence: 59%
“…In considering the implementation of such an approach, it will be essential to assess potentially problematic drug-drug interaction that could alter the pharmacology of FK506 and/or MGX. The CYP3A P450 sub-family is primarily responsible for FK506 metabolism [ 57 ]. Studies are ongoing in regards to the metabolism of fosmanogepix, but trials to date have not found significant MGX CYP3A4 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…According to up‐to‐date knowledge, TAC bioavailability is considerably impacted by hepatic and intestinal CYP3A‐dependent metabolism that is altered by CYP3A genetic variants. Therefore, CYP3A4 and CYP3A5 single‐nucleotide polymorphisms (SNPs) are suggested to notably cause TAC clearance interindividual variability 6 . Seven years ago, based on published evidence supporting this relationship, the CPIC published guidelines for the CYP3A5 genotype and tacrolimus dosing as the CYP3A5*3 variant allele (rs776746) results in non‐functional CYP3A5 enzymes 7 …”
Section: What Is Known and Objectivementioning
confidence: 99%
“…A single published meta‐analysis concluded that the CYP3A4*1B variant has an effect on TAC dosing in adult kidney transplant patients 9 . An important pharmacogenetic aspect is the possible linkage disequilibrium (LD) of CYP3A4*1B with CYP3A5*1 , which may lead to undifferentiated impact and the rapid clearance of TAC 6,8,9 …”
Section: What Is Known and Objectivementioning
confidence: 99%
See 1 more Smart Citation